Use of multispecies (Nannochloropsis oceanica, Artemia franciscana, and Arbacia nigra) approach to assess the quality of marine water from Callao Bay, Peru - Alvariño Flores, Lorena; Castañeda Perez, Luz Genara; Panduro, Grober; Machado da Silva Acioly, Thiago; Carvalho Viana, Diego; Iannacone Oliver, José Alberto (My University, 2025)
Multi-species tests in bioassays offer a holistic view of the ecosystem’s response to toxicity, as different species display varying sensitivities to pollutants. This research aimed to assess the ability of toxicity tests’ to distinguish contamination levels, examine site-specific effects, and investigate seasonal variability. Using a multispecies approach (Nannochloropsis oceanica, Artemia franciscana, and Arbacia nigra), bioassays evaluated marine water quality from Callao Bay in Peru across four sampling areas (Naval School: PA1, Peruvian Marine Institute: PA2, Callao Pier: PA3, and San Lorenzo Island: PA4). These species, with varying sizes and morphologies, are relevant to marine systems and ideal for multispecies toxicity testing, contributing to broader environmental impact discussions. To conduct toxicity bioassays, seasonal evaluations were performed in fall, winter, spring, and summer. Brine shrimp displayed seasonal variations in toxicity values, with notable mortality rates during winter. Nannochloropsis oceanica was the most sensitive species, showing moderate toxicity across seasons. Areas impacted by pollution sources, such as wastewater and maritime traffic, exhibited the highest toxicity levels (PA3 and PA4). These fluctuations underscore the need to consider seasonal and local conditions when assessing organism sensitivity to seawater contaminants. Additionally, they reveal the complex interplay between environmental factors, water quality, and organism responses in marine ecosystems.
Keywords: Acute bioassay; Aquatic toxicity; Ecotoxicology; Heavy metals; Pollution; https://purl.org/pe-repo/ocde/ford#1.00.00